DEVELOPMENT OF MANDAILING NATAL FOLKLORE TEACHING MATERIALS BASED ON LOCAL WISDOM OF MARSALI WITH THE AID OF CANVA ONLINE COMICS - Hasibuan, Nikmah Sari; Pulungan, Husniah Ramadhani; Azelia, Cindy; Hutabarat, Anis Pitria; Nanda, Nanda; Wahyudi, Angga (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
This study aims to develop and test the effectiveness of digital comics based on the Marsali method as an interactive learning medium in introducing Mandailing Natal folklore to students. The Research and Development (R&D) method was used in this study, involving five main stages: analysis, design, development, implementation, and evaluation. The results of the study showed that the use of digital comics developed with the Canva application, as well as involving students in Marsali practices, successfully increased their interest and understanding of folklore. Of the 30 students who participated, 85% reported an increase in interest in folklore after studying the comics, and 90% felt that the comics helped them understand the material. In addition, the evaluation also showed an increase in active participation in class discussions. The use of digital comics based on Marsali has proven to be an effective medium in preserving local culture and enriching student learning through a visual and interactive approach that is relevant to the younger generation. This study concludes that digital comics based on local culture can be an effective tool in education, especially in maintaining the sustainability of folklore and cultural heritage in the digital era.